DENSITIES AND VOLUMETRIC PROPERTIES OF L-ASCORBIC ACID SOLUTIONS IN WATER–ETHANOL MIXTURES AT TEMPERATURES FROM 298.15 TO 318.15 $K$ (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
This paper studies volumetric properties of L-ascorbic acid+ethanol–water ternary systems. The densities of solution of L-ascorbic acid (vitamin C) in ethanol–water mixtures with various compositions have been measured over the available concentration range at temperatures from 298.15–318.15 K. Apparent molar volumes, standard partial molar volumes and transfer partial molar volumes of L-ascorbic acid were determined in ethanol–water mixtures. The competitive intermolecular interactions between molecules of ascorbic acid and components of ethanol–water mixtures are responsible for the irregular volumetric behavior of these systems.
Keywords: L-ascorbic acid, ethanol, appear molar volumes, limiting partial molar volumes, transfer partial molar volumes